Microbiota and Mucosal Immunity in Amphibians - Colombo, Bruno M.; Scalvenzi, Thibault; Benlamara, Sarah; Pollet, Nicolas (Frontiers in Immunology, 2015)
We know that animals live in a world dominated by bacteria. In the last twenty years we have learned that microbes are essential regulators of mucosal immunity. Bacterias, archeas and viruses influence different aspects of mucosal development and function. Yet the literature mainly covers findings obtained in mammals. In this review, we focus on two major themes that emerge from the comparative analysis of mammals and amphibians. These themes concern: i) the structure and functions of lymphoid organs and immune cells in amphibians, with a focus on the gut mucosal immune system; and ii) the characteristics of the amphibian microbiota and its influence on mucosal immunity. Lastly, we propose to use Xenopus tadpoles as an alternative small animal model to improve the fundamental knowledge on immunological functions of gut microbiota.